TLR4 deficiency upregulates TLR9 expression and enhances irinotecan-related intestinal mucositis and late-onset diarrhoea - Wong, Deysi Viviana Tenazoa; Holanda, Renata Brito Falcão; Cajado, Aurilene Gomes; Bandeira, Alessandro Maia; Pereira, Jorge Fernando Bessa; Amorim, Joice Oliveira; Torres, Clarice Sampaio; Ferreira, Luana Maria Moura; Lopes, Marina Helena Silva; Oliveira, Roberta Taiane Germano; Pereira, Anamaria Falcão; Sant'Ana, Rosane Oliveira; et al. (Wiley, 2021)
Background and purpose: Severe diarrhoea, a common gastrointestinal manifestation of anticancer treatment with irinotecan, might involve single nucleotide polymorphisms (SNPs) of toll-like receptors (TLRs), described as critical bacterial sensors in the gut. Here, colorectal cancer patients carrying missense TLR4 A896G (rs4986790) or C1,196T (rs4986791) SNPs and Tlr4 knockout (Tlr4−/−) mice were given irinotecan to investigate the severity of the induced diarrhoea. Experimental approach: Forty-six patients treated with irinotecan-based regimens had diarrhoea severity analysed according to TLR4 genotypes. In the experimental setting, wild-type (WT) or Tlr4−/− mice were given irinotecan (45 or 75 mg·kg−1, i.p.) or saline (3 ml·kg−1). Diarrhoea severity was evaluated by measuring intestinal injury and inflammatory markers expression after animals were killed. Key results: All patients with TLR4 SNPs chemotherapy-treated presented diarrhoea, whereas gastrointestinal toxicity was observed in 50% of the wild homozygous individuals. Mice injected with irinotecan presented systemic bacterial translocation and increased TLR4 immunostaining in the intestine. In line with the clinical findings, Tlr4 gene deficiency enhanced irinotecan-related diarrhoea and TLR9 expression in mice. An increased myeloperoxidase activity and Il-18 expression along with IL-10 decreased production in Tlr4−/− mice also indicated an intensified intestinal damage and inflammatory response. Conclusion and implications: TLR4 deficiency upregulates TLR9 expression and enhances intestinal damage and the severity of late-onset diarrhoea during irinotecan-based treatment. Identifying patients genetically predisposed to chemotherapy-associated diarrhoea is a strategy toward precision medicine.
Keywords: colorectal cancer; diarrhoea; intestinal mucosa; irinotecan; mucositis; single nucleotide polymorphism; toll-like receptor 4